Promotion of remyelination by polyclonal immunoglobulin in Theiler's virus-induced demyelination and in multiple sclerosis. - van Engelen, B G (1994)
Spontaneous remyelination occurs in experimental models of demyelination and in patients with multiple sclerosis, although to a limited extent. This enables the search for factors that promote remyelination. Using the Theiler's virus model of central nervous system demyelination, promotion of remyelination was observed after passive transfer of CNS-specific antiserum and transfer of CNS-specific purified immunoglobulin. Mouse polyclonal immunoglobulin from normal non-syngeneic mice, comparable with the human immunoglobulin preparation, also promotes CNS remyelination in the Theiler's virus model of multiple sclerosis. These experimental findings further bridge the gap with a pilot study that suggests clinical improvement after polyclonal immunoglobulin administration, possibly due to remyelination, in some multiple sclerosis patients with stable, steroid-unresponsive optic neuritis. In view of these experimental and clinical data, the physiological role of myelin in demyelination and remyelination is discussed, and the role of IgG solely as a deleterious molecule in the pathophysiology of multiple sclerosis and experimental demyelination is addressed.